Evaluasi Pressure Drop Pada Sumur Injeksi Uap Di Lapangan Duri Dengan Persamaan Beggs-Brill Dan Moody - Ahmad Riadi S Hasibuan; Bahruddin Bahruddin; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Steam injection is a heat transfer process to petroleum reservoir through multiphase flow of wet steam. Estimating pressure drop in multiphase flow is more difficult than for single-phase flow. Multiphase flow is a complex phenomenon because of the interdependence of various variables that affecting pressure drop such as flow regime, hold up, flow geometry at horizontal, vertical or deviated, flow rate of each phase and the fluid properties of each phase. The purpose of this study is to find out the most appropriate model to calculate the pressure drop in steam injection wells and understand parameters that most affecting pressure drop. Research methodology for this study is descriptive analysis. Field data from 30 injection wells in Duri field are collected and compared with 2 variations of Beggs-Brill and Moody equation, which are the original model and the model with Palmer correction. Both models are translated into a simple computing program using Excel application. Calculation result from the model is compared with the measurement results to understand the deviation or error. As the result of this study, it is shown that Beggs-Brill and Moody model without Palmer correction is suitable for steam injection application. Average error is only 0,2% with a standard deviation of 3,32%. Further information is obtained from the sensitivity analysis that the accuracy of pressure drop calculation is affected by measurement accuracy of the steam flow rate, steam quality and steam temperature. Keyword: Beggs and Brill correlation, Moody diagram, Palmer correction, pressure drop, steam injection.